IMPLEMENTASI PENGAWASAN TEMPAT HIBURAN UMUM BERDASARKAN PASAL 4 PERATURAN DAERAH NOMOR 3 TAHUN 2002 TENTANG HIBURAN UMUM (STUDI KASUS HIBURAN PUB DI KOTA PEKANBARU) - Sopiatun Wahyuni; Evi Deliana; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Implementation of supervision of public entertainment venues especially Pub entertainment that violates Article 4 of Regional Regulation No. 3 of 2002 concerning General Entertainment, in the implementation of supervision carried out by Pekanbaru City Government which is appointed directly by Regional Officials as part of government assistance is the Civil Service Police Unit. The enactment of the Government Regulation of the Republic of Indonesia Number 16 Year 2018 concerning the Civil Service Police Unit affirmed in Article 1 Paragraph 1 The Civil Service Police Unit, hereinafter referred to as the Satpol PP, is a regional apparatus established to enforce Regional Regulations and Regional Head Regulations. community protection. Public entertainment venues specifically Pubs in Pekanbaru City have violated Article 4 of Regional Regulation No. 3 of 2002 concerning General Entertainment and the Pekanbaru Civil Service Police Unit has the duty to control and carry out supervision according to the rules imposed. But the fact is that there are still weaknesses in carrying out supervision carried out by Pekanbaru City Government.This type of research is Sociological Descriptive, in this study the author immediately conducted research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at the MP Executive Club & Karaoke, the Civil Service Police Unit and the Pekanbaru City DPRD, while the population and samples were all parties related to the problem under study. The data sources used are primary data, secondary data and tertiary data, data collection techniques in the study carried out by interviews, digital documentation and literature studies.The results of the study can be concluded that the supervision carried out by the Civil Service Police Unit was directly assessed as not yet firm and weak. There has been no firm effort so far on existing sanctions to be enforced by the Pekanbaru City Government against business owners who violate Article 4 of Regional Regulation Number 3 Year 2002 concerning General Entertainment. This caused many businesses to violate and feel safe in opening Pub.Keywords: Supervision - Pub Entertainment - MP Executive Club & Karaoke - Civil Service Police Unit